Analisis Logam Merkuri (Hg) Pada Krim Pemutih Wajah Merek X Dengan Metode Spektrofotometri Serapan Atom (SSA) - Madania Madania; Megawati M Martani (Study Program of Chemistry - Alauddin State Islamic University of Makassar, 2014)
Whitening creams that supposedly contain mercury which is added with the aim to reduce freckles on the skin’s surface, but it gives a negative impact, for it was conducted analysis of the presence of mercury compounds qualitatively and quantitatively. This research is purely experimental research with the aim of identifying the content of mercury (Hg) is the bleach cream face on brand X circulating in Indonesia are on the label does not have the composition, number and batch number POM and determine levels of mercury (Hg) is the bleach cream face on brand X. Qualitative test using three reagents that NaOH, HCl, KI whereas quantitative testing using atomic absorption spectrophotometry (SSA).The result of the research that brand X contains mercury (Hg). Brand X code A contains 2718,1273 bpm mercury (Hg) and code B contains 214,1661 bpm. Quantitative analysis results calculates using concentration obtained from a linear regression of whitening face cream brand X Code A contains 3239.9117 bpm mercury (Hg) and Code B contains 858,6798 bpm mercury (Hg) in pot.